Effect of Public Investment on Health Population: A Review of BRICS Countries - Shahid, Tanveer Ahmed; Rahman, Saif Ur; Sheikh, Salman Masood; Allahrakha, Rubina (iRASD Journal of Economics, 2024)
This research aims to investigate the perspectives offered by the literature on health population in relation to public investment, Foreign Direct Investment, and Economics Policy Uncertainty in emerging nations. This paper explores and summarizes current theoretical and empirical studies on the issue. It begins by providing a summary of public investment, foreign direct investment, and HP in the BRICS nations. The literature is identified in a second way, utilizing conceptual and practical knowledge from published works. Furthermore, this paper clarified theoretical methodologies that describes how these strategies function. This work advances the fields of public investment, health population, foreign direct investment, and economic policy.